mpt64 mutations in Mycobacterium tuberculosis with negative MPT64 antigen assay results from a tertiary hospital in Southeastern China - Pan, Xinling; Zhou, Sujuan; Jin, Lulu; Ji, Songjun; Lou, Xingxing; Lu, Bin; Zhao, Jin (Frontiers in Medicine, 2025)
BackgroundMPT64 protein is an effective marker for detecting Mycobacterium tuberculosis (MTB) in liquid culture and clinical tissue samples. However, some MTB clinical isolates test negative for this antigen because of varied mutation types across different regions.MethodsDNA samples of MPT64 antigen assay-negative MTB strains were collected from a tertiary hospital from January 2016 to January 2024, and mpt64 gene mutations were detected by sequencing. Clinical records of patients with negative MPT64 antigen results were collected and compared with those of patients with positive results. The global distribution of mpt64 gene mutations was analyzed using MTB genome sequences from the National Center for Biotechnology Information (NCBI) database.ResultsAmong 821 mycobacterial specimens with negative MPT64 antigen assay results, 77 MTB strains were collected from 73 patients. Compared with MPT64-positive patients (n = 301), a higher percentage of MPT64-negative patients had a history of anti-tuberculosis therapy (n = 7, 11.1%; P = 0.01). Moreover, MPT64-negative patients demonstrated a lower percentage of positive Gene Xpert results than MPT64-positive patients (73.8% vs 95.1%, P < 0.001). Several gene mutations were detected in the MPT64-negative MTB strains, including 63 bp deletion, single nucleotide mutations, and IS6110 insertion. Among 7,324 MTB genomes from the NCBI database, 87 strains had mutations in the mpt64 gene sequence, with four common mutation sites causing single amino acid changes, including G34A (8.0%), A103G (27.6%), T128A (9.2%), and C477A (24.1%).ConclusionA negative MPT64 antigen result in MTB cultures can be attributed to mutations in the mpt64 gene, and infections caused by these strains are more likely to be misdiagnosed.